DNA barcode of native apple snail Pila virescens (Deshayes, 1824) (Gastropoda: Ampullariidae) from Madura Island, Indonesia - RENI AMBARWATI; DWI ANGGOROWATI RAHAYU; ULFI FAIZAH; NUR ROHMATIN ISNANINGSIH (Society for Indonesian Biodiversity, 2025)
Abstract. Ambarwati R, Rahayu DA, Faizah U, Isnaningsih NR. 2025. DNA barcode of native apple snail Pila virescens (Deshayes, 1824) (Gastropoda: Ampullariidae) from Madura Island, Indonesia. Biodiversitas 26: 1145-1155. Pila virescens is a native apple snail species in Indonesia that is currently under severe threats that urgently require our attention. This research is therefore crucial in validating P. virescens from Madura Island, using both morphological and molecular data, specifically DNA Barcode Cytochrome Oxidase Subunit 1 (COI). Samples were collected from Tlambah Reservoir, Sampang, Madura. Morphological identification was conducted based on shell characteristics, while molecular characterization was applied based on DNA barcode COI. The 618-base pair (bp) of CO1 gene sequence was used for the analysis of genetic diversity and the reconstruction of a phylogenetic tree. Muscle samples were preserved in pure-grade ethanol and underwent a series of procedures, including DNA extraction, Polymerase Chain Reaction (PCR), and sequencing, all conducted with the utmost care and precision. Sequence data were analyzed using Barcode of Life Data Systems (BOLD) Systems, the Automatic Barcode Gap Discovery (ABGD) web application, and haplotype network analysis. The results showed a high Haplotype diversity (Hd) of 0.09091 and a nucleotide diversity (?) of 0.17676, representing a substantial range of genetic variation. The frequency of parsimony informative sites was recorded at 26.48%, with 18 polymorphic sites identified, leading to a total transition/transversion (ts/tv) ratio of 2.4. Furthermore, the phylogenetic trees had a clear and distinct branching pattern for the cluster P. virescens with another ingroup. These results would significantly enhance the understanding of genetic diversity within the Pila genus, which is crucial for effective conservation efforts.